Experimental Study on Godadhiyukt Shunthi as an Antidote of Bhanga Poisoning in Albino Mice - Dr. Mamata P. Adhao (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Experimental Study on Godadhiyukt Shunthi as an Antidote of Bhanga Poisoning in Albino Mice